Implementasi Kurikulum Merdeka Belajar dalam Meningkatkan Kualitas Pembelajaran di Madrasah Aliyah Muhammadiyah 2 Kedungkandang Malang - Muhammad Afriansyah Novianto; Munirul Abidin (STAI Terpadu Yogyakarta, 2023)
This research aims to analyze curriculum evaluation management in the implementation of the Merdeka Belajar program at Madrasah Aliyah Muhammadiyah 2 Kedungkandang Malang. The research method used is a qualitative approach with data collection techniques through observation, interviews and documentation. The results of the research show that the quality of learning through the independent learning curriculum carried out by Madrasah Aliyah Muhammadiyah 2 Kedungkandang Malang has been implemented well and in accordance with the principles of good evaluation. Evaluations are carried out periodically involving various stakeholders and the evaluation results are used to make curriculum improvements.